(untitled) (Research, Society and Development, 2020)
This article aims to analyze the influence of the individual absorption capacity on the entrepreneurial intention of students of the administration course at a Public University. For this, a quantitative, descriptive and correlational approach was used. Data were obtained from primary sources through a survey with a questionnaire, answered by 158 students. The data were initially treated and analyzed using the statistical software SPSS 20, where normality and sample adequacy tests were performed. Then, structural equation modeling was performed using the SmartPLS 3 software. The results showed that the entrepreneurial intention is influenced by the individual absorption capacity of students in the Administration course. The research contributes with complementary provocations to studies on individual absorption capacity and its interaction with entrepreneurship linked to the university environment, contributes to the strengthening of the business sector that are potential recruiters of university students.